Arctic justice : environment, society and governance - Wood-Donnelly; Ohlsson, Johanna (Spaces and practices of justice, 2023)
Offering a unique introduction to the study of justice in the European, North American and Russian Arctic, this collection highlights the practical consequences of postcolonial legacies and climate change while championing a sustainable future for Arctic development and governance.